The effect of maximalist running shoes on impact loading: a critically appraised topic - Loudon, J. K.; Swift, M. (International Journal of Athletic Therapy & Training, 2022)
Clinical Scenario: Running injuries are common in runners. The use of maximal cushioned shoes (MAX) has been suggested as a preventive measure for reducing impact loading and thus running-related injuries. Clinical Question: Do maximalist running shoes reduce impact loading compared to traditional shoes in runners? Summary of Key Findings: A search was performed for articles exploring MAX on impact loading in runners. Five articles were included in this critically appraised topic. All were case-controlled laboratory studies that compared the MAX to a traditional running shoe. None of the studies found a reduction in impact loading with use of the MAX. Clinical Bottom Line: Based on five case-controlled studies, a MAX does not reduce impact loading on level surfaces or downhill running. Based on mixed results, the MAX may increase impact forces during level and downhill running. Future research should include randomized controlled trials that assess impact forces after the runner has adapted to the MAX and after running ultradistances. Strength of Recommendation: In agreement with the Center of Evidence-Based Medicine, the consistent results from five Level III intervention studies designate that there is Level C evidence that MAX do not reduce impact loading during a single running trial.